Antisipasi Didaktis–Pedagogis Berbasis Learning Obstacle Materi Relasi Rekursif pada Mata Kuliah Matematika Diskrit - Ashari, Nur Wahidin; Mulbar, Usman; Asdar, Asdar (Venn: Journal of Sustainable Innovation on Education, Mathematics and Natural Sciences, 2026)
Discrete Mathematics learning at the university level requires high-level reasoning skills and deep conceptual understanding, particularly in the topic of recursive relations. However, in instructional practice, students still experience various learning difficulties that affect the quality of their understanding. This study aims to identify students’ learning obstacles in recursive relations as a preliminary study within the framework of Didactical Design Research (DDR). A qualitative approach was employed by analyzing students’ responses to true–false items accompanied by written justifications administered in a final examination. The data were analyzed to identify learning obstacles based on ontogenic and epistemological perspectives. The findings indicate that students experience learning obstacles characterized by the inappropriate use of prior mathematical knowledge, limited ability to provide conceptual justifications, and a tendency toward procedural reasoning in contexts that require deeper conceptual analysis. These results suggest that students’ difficulties in recursive relations cannot be separated from the didactical situations framing the learning process. This preliminary study provides a foundation for the development of didactical designs in subsequent research, with the conceptual integration of the Case Method to reconstruct more meaningful learning situations in Discrete Mathematics.